2021
DOI: 10.3126/jnphyssoc.v7i2.38628
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Environmental Radioactivity in Soil Samples from Kathmandu Valley, Nepal

Abstract: This study was conducted to determine the amount of naturally occurring radioactivity in the soil of Nepal's Kathmandu valley. The activity of naturally occurring radionuclides was determined in these soil samples using a sodium iodide detector. Activity concentrations of 238U, 232Th, and 40K were found in the range: 32.00-111.38 Bq kg-1, 33.52-130.04 Bq kg-1, and 342.50-897.71 Bq kg-1, respectively. These values are well within the permissible range as recommended by UNSCEAR. The soil samples with the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The Bagmati province in Nepal presents a significant locale for a study aimed at measuring the background radiation levels, as no prior investigations on natural background radiation have been conducted in this region. However, a recent study has reported on radionuclides found in the sediments [9] and soil [10] of Kathmandu Valley. Situated in the Himalayan mountain range, the region is characterized by ancient crystalline rocks known to harbor radioactive elements.…”
Section: Introductionmentioning
confidence: 99%
“…The Bagmati province in Nepal presents a significant locale for a study aimed at measuring the background radiation levels, as no prior investigations on natural background radiation have been conducted in this region. However, a recent study has reported on radionuclides found in the sediments [9] and soil [10] of Kathmandu Valley. Situated in the Himalayan mountain range, the region is characterized by ancient crystalline rocks known to harbor radioactive elements.…”
Section: Introductionmentioning
confidence: 99%